Democracy at work and perspectives on the quality of working life in scandinavia - Thorsrud, Einar (Research series (International Institute for Labour Studies), 1976)
This study by professor E. Thorsrud is one in a series on developments in the fields of humanisation of work and quality of working life to apper in the research series of the international instute for labour studies.